Potential transmission of leptospirosis from rats and ectoparasites in the Health Office of Port of Surabaya Class I - Wulandari, Indah Sari; Satoto, Tri Baskoro Tunggul; Ristiyanto (BKM Public Health and Community Medicine, 2023)
Purpose: This study attempted to confirm leptospirosis in rats and ectoparasites in the working area of Tanjung Perak Port and the working region of Gresik Port Health Office of Port of Surabaya Class I. Methods: This study is a descriptive study using a cross-sectional approach. The samples were rats. The rats are identified to determine the type, then shaved to take ectoparasites and dissected to take the kidneys. Testing of pathogenic Leptospira bacteria using the ii-PCR method. The study lasted from October 2022 to February 2023. Results: The rat species were Rattus norvegicus. Based on PCR examination, pathogenic Leptospira bacteria were found in the kidneys of rats Rattus norvegicus. Rattus norvegicus was infected with the pathogenic Leptospira bacteria in the Port of Tanjung Perak working area at 56,67% and in the Port of Gresik working area at 43,75%. The ectoparasites found are fleas, lice, and mites. Both study sites did not find Pathogenic Leptospira bacteria in ectoparasites (fleas and mites). Fleas infestation of Rattus norvegicus in the working area of Tanjung Perak Port increased by 80% and in the work area of Gresik Port by 68,75%. Conclusion: The pathogenic Leptospira bacteria was found in both research sites in Rattus norvegicus's kidneys but not in ectoparasites (fleas and mites). Flea infestation is also high in both research locations.